(3GdeLGR aj MbjbI QMdI GdTjN eMeO Rjf GdYGHOjf GdUOjbi Edi GdMLGRs - (3GdHOQ GdeUQj , eMeO Hf CHj HcQ Hf SdjeGf GdTGaYj, HOQ GdOjf,J (B1062 (3g` s
(3ChdgG (B:s
(3hHYO aeG cd WGdH eWdhH hdG cd NGWH eNWhH s
(3BNQgG (B:s
(3hedG bdhH GdYGQajf HQg hMHg hCPGb GdeMHjf dPI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B110s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B428s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdLZQGajG h GdHdOGfs